2022
DOI: 10.1590/fst.242703
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fatigue activities of anthocyanins from Lycium ruthenicum Murry

Abstract: Anthocyanins from Lycium ruthenicum Murry (LRAs) were used to explore the anti-fatigue activities of LRAs at different concentrations in a mouse fatigue model. Eight biochemical indexes were determined in liver tissue, muscle tissue and serum. The results showed that the LRAs used in the experiment mainly contained delphinium, petunidin and malvidin. During 21 days of gavage, there was no significant difference in mouse body weight. The exercise time of the LRA-exposed mice increased. LRAs could increase serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additionally, anthocyanins undergo reactive discoloration in response to pH variations. Utilizing a straightforward approach, intelligent labels can be affixed to filter substrates to enable the swift, non-destructive testing of meat product freshness within packaging, thereby safeguarding consumer health [76].…”
Section: Lrm's Product Development In the Field Of Packaging Technologymentioning
confidence: 99%
“…Additionally, anthocyanins undergo reactive discoloration in response to pH variations. Utilizing a straightforward approach, intelligent labels can be affixed to filter substrates to enable the swift, non-destructive testing of meat product freshness within packaging, thereby safeguarding consumer health [76].…”
Section: Lrm's Product Development In the Field Of Packaging Technologymentioning
confidence: 99%
“…With the advancement of modern pharmacological studies, various biological activities of LRPS have been extensively investigated. Research indicates that LRPS show diverse biological activities, including antioxidant activity [6], anti-fatigue activity [7], anti-tumor activity [8], anti-radiation activity [9], hypoglycemic activity [10], anti-osteoporosis [11], immunomodulatory [12], neuroprotection [13], hepatoprotective activity [14], prebiotic activity [15] and a gastric mucosal protective effect [16].…”
Section: Bioactivitiesmentioning
confidence: 99%
“…The underlying mechanisms include increasing the body's energy substrate reserves, promoting fat utilization for energy, maintaining redox homeostasis, enhancing mitochondrial biogenesis, repairing mitochondrial damage, reducing metabolite accumulation, and inhibiting the accumulation of neurotransmitters [60]. Wang et al [7], through experiments involving weighted swimming, confirmed the anti-fatigue effect of LRPS on normal mice. LRPS extended the swimming time of normal mice, alleviated oxidative stress, lowered post-exercise serum urea and blood lactate levels, increased the reserves of liver glycogen and muscle glycogen, and improved the exercise load capacity of normal mice, making them less prone to fatigue.…”
Section: Anti-fatigue Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Of all alcoholic beverages, wine is an interesting and unique product. Wine may be distinguished from the others by the presence of grape-derived phenolic compounds (Deroover et al, 2021;Miele, 2021;Zhang et al, 2022). Somani et al (2015) suggested that grape polyphenols (including anthocyanins, flavonols, favan-3-ols, stilbene, and phenolic acids) could have anti-inflammatory activities that regulate multiple molecular targets and pathways.…”
Section: Introductionmentioning
confidence: 99%